Brain‐derived neurotrophic factor predominantly regulates the expression of synapse‐related genes in the striatum: Insights from in vitro transcriptomics. Issue 4 (16th September 2021) - Koshimizu, Hisatsugu; Matsuoka, Hidetada; Nakajima, Yoshihiro; Kawai, Anna; Ono, Junichiro; Ohta, Ken‐ichi; Miki, Takanori; Sunagawa, Masataka; Adachi, Naoki; Suzuki, Shingo
Abstract: Aim: The striatum, a main component of the basal ganglia, is a critical part of the motor and reward systems of the brain. It consists of GABAergic and cholinergic neurons and receives projections of dopaminergic, glutamatergic, and serotonergic neurons from other brain regions. Brain‐derived neurotrophic factor (BDNF) plays multiple roles in the central nervous system, and striatal BDNF has been suggested to be involved in psychiatric and neurodegenerative disorders. However, the transcriptomic impact of BDNF on the striatum remains largely unknown. In the present study, we performed transcriptomic profiling of striatal cells stimulated with BDNF to identify enriched gene sets (GSs) and their novel target genes in vitro . Methods: We carried out RNA sequencing (RNA‐Seq) of messenger RNA extracted from primary dissociated cultures of rat striatum stimulated with BDNF and conducted Generally Applicable Gene‐set Enrichment (GAGE) analysis on 10599 genes. Significant differentially expressed genes (DEGs) were determined by differential expression analysis for sequence count data 2 (DESeq2). Results: GAGE analysis identified significantly enriched GSs that included GSs related to regulation and dysregulation of synaptic functions, such as synaptic vesicle cycle and addiction to nicotine and morphine, respectively. It also detected GSs related to various types of synapses, including not only GABAergic and cholinergic synapses but also dopaminergic and glutamatergic synapses. DESeq2 revealed 72 significant DEGs, among which the highest significance was observed in the apolipoprotein L domain containing 1 ( Apold1 ). Conclusions: The present study indicates that BDNF predominantly regulates the expression of synaptic‐function‐related genes and that BDNF promotes synaptogenesis in various subtypes of neurons in the developing striatum. Apold1 may represent a unique target gene of BDNF in the striatum. Abstract : In the present study, we performed transcriptomic profiling of striatal cells stimulated with BDNF to identify enriched gene sets (GSs) in vitro. Generally Applicable Gene‐set Enrichment (GAGE) analysis followed by differential expression analysis for sequence count data 2 (DESeq2) suggested that BDNF predominantly regulates the expression of synaptic‐function‐related genes and that BDNF promotes synaptogenesis in various subtypes of neurons in the developing striatum.